Teacher Education for Inclusive Education: A Scoping Review of Global South Scholarship - Herrera-Seda, C (Routledge, 2025)
Teacher education is important for the successful implementation of inclusive education. Research on this topic has increased in recent years across the world. However, the knowledge produced in Global South countries is relatively less visible and is infrequently cited, despite its potential contribution. To visibilise this knowledge, we conducted a scoping review of journal articles on teacher education for inclusive education research in the Global South. Ninety-five conceptual and empirical studies from 2012 to 2021 from four databases were analysed, and we present findings of the review under the headings of general information, research approaches, research teams, policy referents, funding sources, and results. The findings are discussed with concepts from decolonial theory where we argue that 1) Knowledge production on teacher education for inclusive education in the Global South mostly follows Global North research agendas, methodologies, and theories; 2) Place or context serves as a mere background or site for teacher education for inclusive education, rather than agentic in creating the conditions of teachers’ work; 3) Global South researchers work with limited funding and unstable research conditions, with few cross-southern partnerships. The review indicates a need for critical appraisal of current knowledge formations by teacher education policy-makers, researchers, and practitioners. © 2025 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Inclusive education; teacher education; scoping literature review; global south; decolonisation